Ettringite formation on the aggregate — cement paste interface - Monteiro, J.J.M.; Mehta, P.K. (Cement and concrete research, 1985)
Subject of the experiment was a portland cement paste, with w/c ratio of 0.35, cast against the polished surface of a granite rock, and hydrated for various times. Abrasion and study of the polished paste-rock interfacial zone using QXRD revealed high quantities of ettringite next to the aggregate surface, corroborating the " through-solution" mechanism of ettringite formation.